2014
DOI: 10.1097/lgt.0000000000000003
|View full text |Cite
|
Sign up to set email alerts
|

Cervicovaginal Levels of Proinflammatory Cytokines Are Increased During Chlamydial Infection in Bacterial Vaginosis But Not in Lactobacilli-Dominated Flora

Abstract: Detection of endocervical CT is associated with increased cervicovaginal IL-1β, IL-6, and IL-8 levels in women with concomitant BV but not in those with normal flora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
2
11
0
1
Order By: Relevance
“…This may constitute a possible mechanism by which inflammation contributes to HPV-mediated carcinogenesis. Furthermore, our results are in accordance with data from the literature that have already described the relation between C. trachomatis infection and high-grade cervical lesions (13)(14)(15)(16).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This may constitute a possible mechanism by which inflammation contributes to HPV-mediated carcinogenesis. Furthermore, our results are in accordance with data from the literature that have already described the relation between C. trachomatis infection and high-grade cervical lesions (13)(14)(15)(16).…”
Section: Discussionsupporting
confidence: 83%
“…In conventional Pap smears, Matheus and colleagues (12) showed a high expression of MMP-9 in the presence of genital infections. Herein, we found a significant association between C. trachomatis and high-grade cervical lesions (CIN2/CIN3/SCC; OR, 3.7; 95% CI, 1.3-11.3), which has already been amply demonstrated in the literature (13)(14)(15)(16). In addition, we found that women with C. trachomatis have a 2.7 higher chance of presenting multiple infections than a single infection by HPV, although this result was not statistically significant in this sample size (OR, 2.7; 95% CI, 0.8-9.0).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Mitchell et al reported a relationship between BV and decreased HBD2 expression but no relation to IL-6 (26). On the other hand in Chlamydia trachomatis infection, IL-6 is reportedly increased with BV patients but not with Lactobacillus dominant flora (27). Our results suggested that IL-6 might not be strongly involved in the pathogenesis of BV and Candidiasis in some vaginal environments ( Table 3 and…”
Section: Discussionmentioning
confidence: 60%
“…При воспалительных заболеваниях вульвы и влагалища также отмечается повышение синтеза ФНО-альфа и ИЛ-1, в т. ч. и у беременных пациенток [9][10][11]. Повы шенный цитокиновый фон, высокая активность G. vagi nalis на фоне дополнительной супрессии нормальной микрофлоры влагалища антисептиками могут провоцировать быструю гибель нормальных клеток слизистой в зоне воспаления в результате процесса пироптоза [12,13].…”
Section: патогенетическое обоснование применения бензидамина при острunclassified